An analysis of the transformation of residential interior spaces of selected Filipino widows in Metro Manila - Lansangan, Feliza Denice E.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This qualitative research is an analysis of the transformational effect of widowhood and the bereavement process on the residential spaces of selected Filipino widows. The study was conducted among 5 widowed homeowners in Metro Manila who lived with or married the deceased for a minimum of 5 years. These widows are still living in the same house, did not remarry, are not in any romantic relationship, and were willing to share their experiences and personal spaces. A snowball sampling method was used to establish prior connections with the respondents. A phenomenological research design was used to gather data; which includes an in-depth interview, observations, and a photo documentation of the spaces. An interview was conducted with the use of an observation guide, a voice recorder, and a camera. Data from the interviews were transcribed and thematically tabulated using narrative analysis guided by secondary data and the theories of Sense of Place, Design Narrative Theory, and Therapeutic Landscapes. The results of the study showed that spaces were transformed through a change in function and use of space, space planning and modification of furniture pieces. The reasons for such changes were due to maintenance costs, to change the mood of the interior, and to retain or add decorations with symbolic meaning. Each widow had a unique way of coping with the bereavement process, highly influenced by support from family and their religious affiliation. Private spaces were transformed due to psychological needs such as sense of security and protection, whereas public spaces were transformed due to physiological needs such as maintenance and functionality. Personal healing was seen through changes and adaptations made in the space. The transformation was observed from the narratives of the spaces, the meanings re-assigned to them, and changes in the widow's experience related to practicality, and issues in protection and independence.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Widows -- Philippines